Knowledge, Attitude and Behaviors of Adults About_x000D_ Adulthood Immunization - UZUNER, ARZU (My University, 2018)
Background and Objective: While newborn and childhood vaccination is widely known and utilized worldwide, adult immunization is not applied widely.Therefore, about 30,000 adults die yearly from preventable diseases. The routine vaccination of adults are considered unsatisfactory also in our country. Theaim of this research is to evaluate the knowledge, attitude and behaviors of adults about adulthood immunization in Maltepe, Istanbul. Methods: Anobservational and descriptive study was carried out in Maltepe, Istanbul between March 20th and May 6th, 2016 in a total of 16 family health centers whichwere randomly selected from each neighbourhood. A questionnaire form inquiring the socio-demographic characteristics, knowledge, attitude and behaviorsabout adult immunization was applied with face-to-face interviews to participants who were over the age of eighteen. Results: A total of 318 participants wereincluded in the study. Of the participants, 222 females (69,8%) and 96 were males (30,2%). Mean age was 43,4±15,8 years (min. 18, max. 87). Educationlevel was high school and above in 55% of the subjects. The most commonly known vaccine was the influenza vaccine (89,3%), the least known vaccine wasthe shingles vaccine (32,3%). While tetanus vaccine was the most commonly used (42,1%) followed by, the 23,9% for influenza (23,9%), and hepatitis B(18,2%) , 0,3% (n=1) had been vaccinated for HPV. The confidence for the effectiveness of the vaccines was the highest for hepatitis B (60,4%), and thelowest for influenza (40,9%) and HPV (48,1%). Media was the most commonly used source of knowledge about adult vaccination (27,7%). A statisticallysignificant difference was not detected between the patients who had/did not have a chronic disease or the patients who were using medications regularly ornot with regard to vaccination against influenza, pneumococcus and tetanus (p>0.05). The most common reasons for not getting vaccinated were “havinginsufficient knowledge about the vaccine” (42,5%) and “deeming it unnecessary” (41,2%). Conclusion: The results of the study have revealed that theparticipants did not have sufficient knowledge about adult vaccination and vaccination rates were low. So it may be targeted to improve the knowledge levelof the community through using media and primary care institutions as effective sources of knowledge.

Giriş ve Amaç: Yenidoğan ve çocukluk dönemi aşıları hakkında tüm dünyada farkındalık ve uygulamalar varken, erişkin aşılamaları yaygın uygulama alanına_x000D_ sahip değildir. Bundan dolayı erişkin dönemde aşıyla önlenebilen hastalıklardan dolayı ölümler dünya çapında yılda 30.000 kişiyi bulmaktadır. Ülkemizde de_x000D_ erişkinlerin rutin bağışıklaması eksik kabul edilmektedir. Bu araştırmanın amacı Maltepe ilçesindeki erişkinlerin erişkin aşıları hakkındaki bilgi, tutum ve_x000D_ davranışlarını değerlendirmektir. Gereç ve Yöntem: Araştırma İstanbul Maltepe ilçesinde 20.03-06.05.2016 tarihlerinde gözlemsel ve tanımlayıcı olarak_x000D_ gerçekleştirildi. Maltepe ilçesinin 16 mahallesinin her birinden randomizasyonla belirlenen toplam 16 Aile Sağlık Merkezi (ASM)’nde yürütüldü._x000D_ Sosyodemografik özellikleri ve erişkin aşıları hakkında bilgi, tutum ve davranışları sorgulayan bir anket formu belirlenen tarihler arasında başvuran 18 yaş_x000D_ üzerindeki bireylere yüz yüze görüşme yöntemiyle uygulandı. Bulgular: Araştırmaya toplam 318 kişi dahil edildi. Katılımcıların 222’si (%69,8) kadın, 96’sı_x000D_ (%30,2) erkekti. Katılımcıların yaş ortalaması 43,4± 15,8 yıl (minimum 18- maksimum 87), %55’inin eğitim düzeyi lise ve üzeriydi. En çok bilinen aşı grip_x000D_ aşısı (%89,3), en az bilinen aşı zona aşısıydı (%32,3). Erişkin dönemde katılımcıların en çok yaptırdığı aşı tetanoz (%42,1), grip (%23,9), Hepatit B_x000D_ (%18,2)aşısı iken en az yaptırılan aşıysa HPV (%0,3) aşısı olarak saptandı. Aşıların koruyuculuğuna güvenme oranı en yüksek sıklıkta Hepatit B (%60,4)_x000D_ aşısında, en düşük oranda grip (%40,9) aşısı için belirtildi. Erişkin aşıları hakkında en çok bilgi edinilen kaynak medyaydı (%27,7). Kronik hastalığı_x000D_ olan/olmayan ve düzenli ilaç kullanan ya da kullanmayanlar arasında grip, tetanoz ve pnömokok aşılarını yaptırma açısından anlamlı düzeyde fark saptanmadı_x000D_ (p>0.05). Aşıları yaptırmayanların en çok belirttiği gerekçeler aşı hakkında bilgilendirilmemiş olma (%42,5) ve aşıyı kişisel olarak gerekli görmemiş (%41,2)_x000D_ olmalarıydı. Sonuçlar: Araştırma, katılımcıların erişkin aşıları hakkında yeterli düzeyde bilgi sahibi olmadıklarını ve aşılanma oranlarının düşük olduğunu_x000D_ ortaya koymuştur. Buna göre halkın erişkin aşıları hakkında bilgi düzeyinin arttırılması hedeflenebilir. Bu amaçla etkili bilgi kaynağı olarak medya ve birinci_x000D_ basamak sağlık kurumları kullanabilir.
Erişkinlerin Erişkin Aşıları Hakkındaki Bilgi, Tutum ve Davranışları